Keputusan Nasabah Dilihat dari Kualitas Layanan dan Promosi Pada PT. Bank BPR Cincin Permata Andalas Cabang Padang - Romi Susanto (JURNAL PUNDI, 2021)
Fast traslate Icon translate The research aimed to know the impact of service quality and promotion on costumer decision of PT. Bank BPR Cincin Permata Andalas Cabang Padang. Using of this sample is 91 poeple costumer use technic Rumus Slovin. Method of collect data is using questioner. The anlyst technic is instrument test, anlyst descreptive, classic assumption test, doble linier anlyst and hypothesis test. Based of test hypothesis found of tangible, responsivness, and assurance not affect positive and significant to constumer decision. Realibility, emphaty and promotion has positive and significant affect to constumer decision.  Suggest to company to more attention the service quality and promotion to custumer candidate that more better and the custumer more interesting to use insurance in the future.